“Mucho más que una fábrica de humores”:1 propuestas literarias y pedagógicas para un taller sobre menopausia (Altre Modernità, 2020)
In Western culture, from Aristotle to the present day, there has been no lack of authors who have referred to climacteric as a problem, an illness, a situation in which medical intervention becomes essential to recover a lost balance (Perz and Ussher, Nosek). Following Serrano and considering menopause as an enriching and fundamental stage in the physical and psychological evolution of each woman, this paper aims to contribute to the emerging studies of Narrative Medicine in Spain (Marrero Díaz 18) by giving back the power of narration (Charon, Covelli) to female voices and telling this stage from an holistic point of view (Murphy et al) focused on empowerment (Pennebaker and Seagal, Capote Bueno et al.). Based on this, we propose a review of the poetic literature on this topic in the Hispanic context, in order to use it as a springboard for the creative expression of the participants of a workshop on narrative medicine implemented in a reference gynecological hospital in southern Spain.
Keywords: Menopause; climacteric; feminism; literature; narrative medicine; literary pedagogy